Prevalence of Dermatophyteic Infection in A Tertiary Care Hospital in Chennai in India: Life Sciences -Microbiology - M.S, Nandini; D, Bindu.; Puhazhendi (International Journal of Life Science and Pharma Research, 2023)
Dermatophytes are fungi that infect keratinized tissues in animals and humans. The group's most prevalent and only anthropophilic species is Trichophyton rubrum, whereas species from the Trichophyton mentagrophytes complex are zoophilic and anthropophilic. The prevalence of dermatophyte infections varies depending on environmental factors and location, with higher rates observed in tropical countries like India. Hence, this study was conducted to comprehend the distribution of various species and clinical symptoms to assess the prevalence and features of dermatophyte infections in patients receiving tertiary care. This study's main objective was to identify the frequency of dermatophyte species in clinical samples taken from suspected patients in a tertiary care centre.1000 patients attending Sree Balaji Medical College in Chennai were the subjects of cross-sectional observational research. The prevalence of dermatophyte infection was assessed using clinical sample data. The analysis included information on gender, age group, and clinical symptoms. In the examined samples, dermatophyte infection was shown to be clinically prevalent (14.2%). More men (64.7%) than women (35.2%) were impacted. The most common age group for dermatophyteic infection was those between 31 and 40 years. The most typical clinical presentation was tinea corporis, characterized by scaly, red areas on the skin. The most frequent dermatophyte species found was Trichophyton rubrum. The study revealed that the clinical samples taken from the tertiary care centre had a significant prevalence of dermatophyteic infection. These infections were more likely to affect men and those in the age range of 31 to 40 years. The most commonly noticed clinical sign was tinea corporis, caused by Trichophyton rubrum. These findings emphasize the need to detect and treat dermatophyteic infections, particularly tinea corporis, highlighting the need for suitable treatment techniques in the population under study.